Implementasi Strategi Pemasaran Digital pada Marketplace untuk Meningkatkan Brand Awareness PT. Ilock Nusantara Indonesia - Cuandra, Fendy; Christina, Christina (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2026)
The use of digital marketing through online marketplaces has become increasingly important for businesses to introduce products and build brand awareness. PT. Ilock Nusantara Indonesia is a company engaged in home security products; however, the utilization of the Shopee marketplace as a digital marketing medium had not been fully optimized. This practical work activity was conducted to assist the company in implementing digital marketing strategies through a marketplace as an initial effort to enhance brand awareness. The methods applied included observation and interviews with the company, product uploading, catalog arrangement, product description development, and product categorization based on type. The results indicate that the Shopee store of PT. Ilock Nusantara Indonesia has become more organized and informative, with a total of 44 products successfully uploaded. Although no sales had occurred at the time of reporting, the store and products were already accessible through the marketplace search feature. This reflects an improvement in product visibility and serves as an initial step in building the company’s digital brand awareness.